Multi-level Parallelization for Hybrid ACO - Abdelkafi, Omar; Lepagnot, Julien; Idoumghar, Lhassane (Swarm Intelligence Based Optimization, 2014)
The Graphics-Processing-Unit (GPU) became one of the main platforms to design massively parallel metaheuristics. This advance is due to the highly parallel architecture of GPU and especially thanks to the publication of languages like CUDA. In this paper, we deal with a multi-level parallel hybrid Ant System (AS) to solve the Travelling Salesman Problem (TSP). This multi-level is represented by two parallel platforms. The first one is the GPU, this platform is used for the parallelization of tasks, data, solution and neighborhood-structure. The second platform is the MPI which is dedicated to the parallelization of programs. Our contribution is to use these two platforms to design a hybrid AS with a Local Search and a new heuristic.